First surface velocity maps for glaciers of Monte Tronador, North Patagonian Andes, derived from sequential Pléiades satellite images. Issue 229 (2015) - Ruiz, L.; Berthier, E.; Masiokas, M.; Pitte, P.; Villalba, R.
Abstract: We apply cross-correlation to Pléiades satellite images to generate accurate, high-resolution monthly surface velocity maps of Monte Tronador glaciers between March and June 2012. Measured surface displacements cover periods as short as 19 days, with a precision of ∼0.58 m (11 m a −1 ). These glaciers follow a radial flow pattern, with maximum surface speeds of ∼390 m a −1 associated with steep icefalls. The lower reaches of the debris-covered tongues of Verde and Casa Pangue glaciers are almost stagnant, whereas Ventisquero Negro, another debris-covered glacier, shows acceleration at the front due to calving into a proglacial lake. Low-elevation debris-covered glacier tongues show increasing velocities at the beginning of the accumulation season, whereas higher-elevation, clean-ice tongues reduce their speed during this period. This contrasting behavior is probably in response to an increase in water input to the subglacial system from winter rainfall events at low elevations and a decrease in meltwater production at higher elevations. These sequential velocity maps can help to identify the controls on glacier surface velocity, aid in the delimitation of ice divides and could also contribute to more realistic calibration of ice-flux-mass–balance models in this glacierized area.